A comparative case study of refugees from Myanmar and Pakistan and their media use in Malaysia: a uses and gratifications perspective - Mokhtar, Aida; Mohd Rashid, Nurul Miza (2017)
A refugee is defined as a person who encounters the fear of being persecuted for their race, religion, nationality, membership of a particular social group or political opinion and resides away from his or her own country and is not willing to be protected by the country, mentions the 1951 Convention Relating to the Status of Refugees, Article 1(A)(2). According to the United Nations Refugee Agency Malaysia (UNHCR), as at the end of August 2017, there are some 149,100 refugees and asylum-seekers registered with the organisation in Malaysia. Most refugees are Rohingyas (61,000 people) and Chins (9,900) from Myanmar and other refugees are mostly from Pakistan (4,200 people). There has been a dearth of research studies on media and refugees in Malaysia but there is great intrigue regarding their media use given their circumstances. The purpose of the research study is to examine the needs of refugees from Myanmar and Pakistan that are gratified by the media as they are residing in Malaysia. The study is qualitative in nature and will comprise interviews on adult refugees who have been in Malaysia for at least six months. The uses and gratifications theory (U&G theory) will be used to frame the research study. The literature suggests that the theory aims to explain the psychological needs that motivate people to meet their intrinsic needs through media use against a socio-cultural background. It is hoped that the study will help develop the theory, contribute to the literature and provide us with an insight of the media use of refugees from Myanmar and Pakistan as the target audience of media messages.